2023
DOI: 10.18280/acsm.470101
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Acacia Mangium Tree Branches as Particleboard Material

Abstract: The quality of particleboard made from broad-leaved acacia branches and PVAc adhesive was investigated. A non-factorial completely randomized design (CRD) with adhesive contents of 10%, 15%, and 20% was employed. The parameters for testing physical properties included moisture content, density, water absorption, and thickness swelling. The parameters for testing the mechanical properties were modulus of elasticity, modulus of rupture, internal bonding, and screw withdrawal resistance. The results indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…V. arborea Buch.-Ham contains more than 68% holocellulose, 40% α-cellulose, 24% lignin, and 0.6% ash [10]. Its specific gravity ranges between 0.40 and 0.60 [11]. Nevertheless, a preliminary study showed it generated low strength particleboard [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…V. arborea Buch.-Ham contains more than 68% holocellulose, 40% α-cellulose, 24% lignin, and 0.6% ash [10]. Its specific gravity ranges between 0.40 and 0.60 [11]. Nevertheless, a preliminary study showed it generated low strength particleboard [12].…”
Section: Introductionmentioning
confidence: 99%
“…of 70/30 using 10% PVAc. Meanwhile, the highest value (0.134×10 4 kgf.cm -2 ) was obtained by that with a ratio of 50/50 using 20% PVAc, which is still lower than the MoE values of acacia-based particleboard using 20% PVAc[11] and composites fabricated from Eleocharis dulcis with ureaformaldehyde adhesive[16] of 2.47×10 4 and 10.750×10 4 kgf.cm -2 , respectively. However, these values have not met the Indonesian National Standard (SNI) 03-2105-2006[8], which requires a value at least 2.04×10 4 kgf.cm -2 .…”
mentioning
confidence: 99%